Актуальные проблемы обучения математике в школе и вузе в свете идей Л. С. Выготского - Боженкова, Людмила; Егупова, Марина (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The article gives a brief overview of the scientific results of the III  International Conference held in Moscow State Pedagogical University in November 2016. The main directions of the development of ideas of L. S. Vygotsky, presented in the reports of leading Russian and foreign scientists - participants of the conference.